Pulmonary Infections in Pregnancy - Mathad, Jyoti S.; Gupta, Amita (Seminars in Respiratory and Critical Care Medicine, 2017)
Pregnant women experience physiological and immunological changes that increase the risk or severity of certain pulmonary infections. These changes also affect drug disposition, which impacts treatment choices. In this article, we review the available data on (1) the physiological and immunological changes that specifically impact tuberculosis, influenza, and varicella pneumonia; (2) active and latent tuberculosis management, including drug monitoring and maternal–infant outcomes; (3) the treatment and prevention of influenza; and (4) the diagnosis and management of varicella pneumonia. Clinical trials often exclude pregnant women, but there is a consensus that treating pregnant women for tuberculosis, influenza, and varicella pneumonia improves outcomes for both the woman and her child.
Keywords: infection; pregnancy; tuberculosis; influenza; pneumonia